Advances and Potentials of Polydopamine Nanosystem in Photothermal-Based Antibacterial Infection Therapies - Fan, Shuhao; Lin, Wensen; Huang, Yifan; Xia, Jiaojiao; Xu, Jun-Fa; Zhang, Junai; Pi, Jiang (Frontiers in Pharmacology, 2022)
Bacterial infection remains one of the most dangerous threats to human health due to the increasing cases of bacterial resistance, which caused by the extensive use of the current antibiotics. Photothermal therapy (PTT), similar to photodynamic therapy (PDT), can generate heat energy under the excitation of light of specific wavelength, resulting in overheating and damage to target cells or sites. Polydopamine (PDA) has been proved to show plenty of advantages, such as simple preparation, good photothermal conversion effects, high biocompatibility, easy functionalization and adhesion, etc. Taking these advantages, dopamine is widely used to synthesize PDA nanosystem with excellent photothermal effect, good biocompatibility and high drug loading ability, which therefore are serving more and more important roles for anti-cancer and anti-bacteria treatment. PDA nanosystem- mediated PTT has been reported to induce significant tumor inhibition, as well as bacteria killings due to PTT induced hyperthermia. And combined with other cancer or bacteria inhibition strategies, PDA nanosystem- mediated PTT can achieve more effective tumor and bacteria inhibitions. In this review, we summarized the progress of preparation methods for PDA nanosystem, followed by the advances of their biological functions and mechanisms for PTT uses, especially in the field of anti-bacterial treatments. We also provided the advances about how to combine PDA nanosystem- mediated PTT with other anti-bacteria methods for synergistic bacteria killings. Moreover, we further provide some prospects of PDA nanosystem-mediated PTT against intracellular bacteria, which might be helpful to facilitate their future research progress for anti-bacterial therapy.